The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1155/2019/1073782
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic, Demographic, and Environmental Determinants of Under-5 Mortality in Ethiopia: Evidence from Ethiopian Demographic and Health Survey, 2016

Abstract: Background. Though Ethiopia has made impressive progress in reducing child mortality in the past two decades, the reduction of under-five mortalities is a major concern for the Sustainable Development Goals (SDGs) introduced in 2016 targeted to reduce under-5 mortality rate below 25 deaths of under-5 per 1,000 live births by 2030. This study aims to assess the risk factors attributed to under-five mortalities in Ethiopia region based on Ethiopian Demographic Health Survey 2016 dataset. Methods. The study was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
44
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 22 publications
19
44
3
2
Order By: Relevance
“…They had increased the death rate by 60%.But, there was no statistically signi cant difference between children were born in home with compared children were born in public health sector. This nding inconsistent with prior studies by (14)(15)(16).…”
Section: Discussioncontrasting
confidence: 99%
“…They had increased the death rate by 60%.But, there was no statistically signi cant difference between children were born in home with compared children were born in public health sector. This nding inconsistent with prior studies by (14)(15)(16).…”
Section: Discussioncontrasting
confidence: 99%
“…The main advantage of HDSS data are; it has very high statistical power, measures trend over time, and track real time data and therefore provide a clear picture of demographic and health progresses. So far in Ethiopia, a number of studies [18,19] have been conducted regarding under-five mortality. Yet, evidence from populationbased longitudinal studies on under-five mortality is limited.…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, the global world health statistics reported that the most important causes of under-five mortalities were preterm birth complications (17%), pneumonia (15%), birth asphyxia (11%), diarrhea (9%), malaria (7%), congenital anomalies (7%), and neonatal infections (15%). Removal of these preventable child deaths requires information about healthcare service utilization on the major causes of deaths [6,7]. In Ethiopia, UNICEF global data reported pneumonia (20.8%), diarrhea (15%), intrapartum (12.3%), preterm (9.6%), and meningitis (7.6%) as the leading cause of deaths among children in 2000.…”
Section: Introductionmentioning
confidence: 99%